2011
DOI: 10.1097/mcg.0b013e318214ab5d
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Lamivudine-Adefovir Therapy in Chronic Hepatitis B Cirrhosis

Abstract: Decompensated chronic hepatitis B cirrhotics may suffer early mortality despite antiviral treatment, and therefore should be considered for early liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…With conventional standard of care in cirrhosis without antiviral therapy, the risk of decompensation was 2 % to 5 % per year, 5-year cumulative incidence of HCC was 10 % to 17 %, and 5-year survival rate was 15 % after decompensation [4]. Lamivudine and adefovir has been extensively evaluated in HBV cirrhosis and shown to improve clinical, biochemical, and virological parameters [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…With conventional standard of care in cirrhosis without antiviral therapy, the risk of decompensation was 2 % to 5 % per year, 5-year cumulative incidence of HCC was 10 % to 17 %, and 5-year survival rate was 15 % after decompensation [4]. Lamivudine and adefovir has been extensively evaluated in HBV cirrhosis and shown to improve clinical, biochemical, and virological parameters [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic HBV carriers may develop chronic hepatitis, cirrhosis, and HCC with HBV as the most frequent cause (Jayakumar et al, 2012). The goal of therapy of chronic hepatitis B is to achieve a sustained suppression of HBV replication, to obtain remission of the underlying liver disease and thus prevent its progression towards cirrhosis and HCC (Lim et al, 2011). Continuous viral suppression is equally essential in order to avoid the risk of the emergence of antiviral resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all patients can achieve cirrhosis recompensation by inhibiting HBV replication. Some patients still have bad prognosis [ 30 , 31 ]. Jang et al [ 18 ] reported that, among 295 patients with decompensated hepatitis B cirrhosis who had started antiviral therapy at the time of first decompensation, 20 patients (6.8%) died of cirrhosis-related complications within six months of antiviral therapy.…”
Section: Issues and Challengesmentioning
confidence: 99%